1985
DOI: 10.1016/s0006-3495(85)83807-8
|View full text |Cite
|
Sign up to set email alerts
|

Capacitative transients in voltage-clamped epithelia

Abstract: In voltage-clamped epithelia the cell membrane potential transient during a + 10-mV transepithelial pulse conforms to the expected behavior for a series combination of two linear resistance-capacitance (RC) circuits. The evolution of the cell potential is characterized by a single time constant with values of 30-130 ms in frog skin and Necturus gallbladder. These observations have important consequences for the measurement of cell membrane resistance ratios and the interpretation of current-voltage relations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1986
1986
1991
1991

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…On the other hand, estimates of intracellular CI activities (Nagel, Garcla-Diaz, and Armstrong, 1981;Gir~tldez and Ferreira, 1984) indicate that for a CI current the reversal should occur at a V v some 38 mV more positive than Vc. Although the actual values of Vc for these experiments were not measured, they are likely to be near the observed reversal potentials (Garcia-Diaz et al, 1985), suggesting that K is the major ion crossing this channel.…”
Section: Single Channel Currentsmentioning
confidence: 84%
See 2 more Smart Citations
“…On the other hand, estimates of intracellular CI activities (Nagel, Garcla-Diaz, and Armstrong, 1981;Gir~tldez and Ferreira, 1984) indicate that for a CI current the reversal should occur at a V v some 38 mV more positive than Vc. Although the actual values of Vc for these experiments were not measured, they are likely to be near the observed reversal potentials (Garcia-Diaz et al, 1985), suggesting that K is the major ion crossing this channel.…”
Section: Single Channel Currentsmentioning
confidence: 84%
“…These structural observations, together with the demonstration of the syncytial behavior of the epithelium (Rick et al, 1978) and the large capacitance of the basolateral membrane of the intact epithelium (Smith, 1971 ;Garcia-Dfaz and Essig, 1985;Schoen and Erlij, 1985) indicates that, functionally, all innermost cell membranes behave as basolateral membrane. This implies that the majority of isolated cells will exhibit macroscopic properties that correspond to the basolateral membrane of the intact epithelium and there would be a much higher probability of recording single channels of basolateral origin/ One can also make the argument that, since the apical membrane of R. pipiens skin does not exhibit any significant conductive permeability to ions other than Na (Helman and Fisher, 1977;Nagel, 1977;Garcia-Diaz et al, 1985;Stoddard, Jakobsson, and Helman, 1985;D6rge, Beck, Wienecke, and Rick, 1989) the K and CI selective channels found in this study are necessarily of basolateral origin.…”
Section: Origin Of K and CL Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…By averaged 33 msec so that by 100 msec (3 • r) capacitative transients are essentially (95%) dissipated. Employing a similar approach, Garcia-Diaz and Essig (1985) have found that r is approximately 50 msec for Necturus gallbladder cells.…”
Section: Discussionmentioning
confidence: 99%
“…polarization) take place. This was accomplished as follows: Assuming that, to a first approximation, the transcellular pathway can be represented by two linear resistancecapacitance (RC) circuits arranged in series, then when a current pulse is passed across the tissue sufficient to clamp ~jms from zero to a new value (Sqjms) (within 2 msec) ~mc will change with a time course given by DeLong & Civan, 1984;Garcia-Diaz & Essig, 1985) Thus, at t = 0, f(t) is equal to f~ (i.e., the fractional capacitance of the basolateral membrane) and when t = ~, f(t) = f,. (i.e., the fractional resistance of the apical membrane).…”
Section: Capacitative Transients: Determination Of the Fractional Capmentioning
confidence: 99%